Microbial Synthesis of Non-Natural Anthraquinone Glucosides Displaying Superior Antiproliferative Properties - Trang Thi Huyen Nguyen; Ramesh Prasad Pandey; Prakash Parajuli; Jang Mi Han; Hye Jin Jung; Yong Il Park; Jae Kyung Sohng (Molecules, 2018)
Anthraquinones, naturally occurring bioactive compounds, have been reported to exhibit various biological activities, including anti-inflammatory, antiviral, antimicrobial, and anticancer effects. In this study, we biotransformed three selected anthraquinones into their novel O-glucoside derivatives, expressing a versatile glycosyltransferase (YjiC) from Bacillus licheniformis DSM 13 in Escherichia coli. Anthraflavic acid, alizarin, and 2-amino-3-hydroxyanthraquinone were exogenously fed to recombinant E. coli as substrate for biotransformation. The products anthraflavic acid-O-glucoside, alizarin 2-O-β-d-glucoside, and 2-amino-3-O-glucosyl anthraquinone produced in the culture broths were characterized by various chromatographic and spectroscopic analyses. The comparative anti-proliferative assay against various cancer cells (gastric cancer-AGS, uterine cervical cancer-HeLa, and liver cancer-HepG2) were remarkable, since the synthesized glucoside compounds showed more than 60% of cell growth inhibition at concentrations ranging from ~50 μM to 100 μM. Importantly, one of the synthesized glucoside derivatives, alizarin 2-O-glucoside inhibited more than 90% of cell growth in all the cancer cell lines tested.